The Effect of Providing Self-Breast Examination (SADARI) Educational Videos on The Level of Sadari Knowledge among Adolescent Girls in Kebonromo Village, Ngrampal District, Sragen Regency - Lestyani; Siti Rofiatun Rosida (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2023)
The objective of this study is to determine the influence of providing SADARI educational videos on the SADARI knowledge level. This research employs a quasi-experimental design, specifically a quantitative one-group pretest-posttest with a cross-sectional approach. Data analysis is conducted using the Wilcoxon test. The population in Kebonromo village comprises 153 adolescent female respondents, and the sample is selected through simple random sampling, involving 60 respondents. The pretest results indicate that one respondent has sufficient knowledge, while 59 respondents have insufficient knowledge. In the posttest, 47 respondents exhibit good knowledge, and 13 respondents have sufficient knowledge. Bivariate analysis using the Wilcoxon test reveals Asymp.Sig (2-tailed) with a significance value of 0.000. In conclusion, there is an influence of SADARI education with video on the SADARI knowledge level among adolescent girls in Kebonromo village, Ngrampal district, Sragen regency.